STRUCTURAL DESIGN AND OPTIMIZATION OF FUNCTIONALLY GRADED MATERIAL ENERGY ABSORBING BOX - ZHANG QingYong; WANG YuChao; WANG Hui (Jixie qiangdu)
The structure design of traditional energy absorbing box has some shorteomings, such as failure to realize stable and orderly folding and collapsing during collision and poor energy-absorbing ability in unit mass, which limits the improvement of automobile safety performanee. The aluminum alloy was added into the traditional 316L stainless steel composition to form afunetionally graded material (FCM) structure of the energy obsorbing box, and the cross section was optimized to be a stick insect tibia cross-sectional structure. The cross section of the energy absorbing box is then optimized by multiple objectives based on the optimized Latin hypercube experimental design and response surface model. The results show that the optimized bionic funetionally graded energy absorbing box can be folded and collapsed stably from head to tail. In addition, the energy-absorbing effect in unit mass was also improved as compared to the traditional energy absorbing box. The results indieate that the damage of the car body in collision can be effectively weakened by the FGM and bionie designed energy absorbing box.